Head–neck melanoma: Clinical, histopathological and prognostic features of an Italian multicentric study - Giusy Schipani; Steven P. Nisticò; Pietro Quaglino; Simone Ribero; Giuseppe Gallo; Vincenzo Maione; Giampiero Girolomoni; Paolo Rosina; Mauro Alaibac; Francesco Messina; Alessandro Gatti; Giuseppe Stinco; et al. (JEADV Clinical Practice, 2024)
Abstract Background Primitive location of melanoma could be a relevant prognostic factor. As regards the scalp, some studies indicate a particularly aggressive biological behaviour for this anatomical localisation. Objectives In this multicentric study, data regarding head–neck melanoma (HNM) have been revised. Methods The design of the study included two main phases. In this retrospective study, data regarding HNM have been collected and analysed. Results In summary, our data suggest that the posterior neck is the area most affected by thicker melanomas. Cheeks and neck melanoma are associated with reduced disease‐free years of life and overall survival compared with all other sites of HNM. Conclusions This study provides useful information in defining the clinical features of HNM, thus improving diagnosis and treatment strategies.